INTERAKSI SOSIAL SISWA TUNADAKSA DENGAN TEMAN KELAS SEBAYA DI SEKOLAH - Fidienillah, Fatihah Fahmi; Rafsanjani, Hanum Syifa; Iqlima, Fairisa (LPPM Universitas Bina Bangsa, 2024)
Children with special needs, including those with disabilities, play an important role in diverse educational environments. Their interactions with classmates and peers play a crucial role in their learning experience at school. This article aims to explore how the social interaction of disabled students in schools occurs. This research uses a descriptive qualitative research approach, with data collection methods through literature review. The data collected focused on literature studies or literature reviews centered on the interaction of students with disabilities. The results showed positive social interaction, where students with disabilities were actively involved in various activities with peers, both inside and outside the classroom